BBC Learning English Channel in Listening Skill of EFL Classroom - Aini, Nurul; Abdillah, Ericha Cahya; Nurhandayani, Nevita (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The BBC Learning English Channel provides some audio and video resources dedicated to English language learners, making it a potentially useful tool in EFL courses especially in “6 Minutes English” section. This study analyses the students’ perception on using BBC Learning English as a way to learn listening. This study aims to determine how students’ perception on using BBC Learning English. The researchers use a descriptive qualitative research approach as a design to analysis the data using a semi-structured interview with the six-item questions as the research instrument. There are 11 EFL students, as the respondents were chosen at the university level. The study shows that BBC Learning English can be used as the media to learn listening skill. The result of this study shows that students get some benefits when they watch and listen to the content in BBC Learning English Channel whether it is about listening skill. In conclusion, learning listening skills through BBC Learning English can enhance listening and learning the British accent as well. Using BBC Learning English makes the process of learning effective and motivates students to learn more about English, so it can be used as an alternative way of learning listening